Optimization and Characterization of Melamine Urea Formaldehyde (MUF) Based Adhesive With Waste Rubber Powder (WRP) as Filler - Nitthiyah, Jeyaratnam (2013)
Fillers are added in adhesive formulation to minimize the utilization of resin in wood based products. Waste Rubber Powder is being used as wood adhesive filler in order to change the research work from waste to wealth. In this work, Melamine Urea Formaldehyde (MUF) resin was produced in the laboratory and waste rubber powder was subjected to chemical modification by using oxidizing agents such as 20% nitric acid, 30% hydrogen peroxide and acetone solution were added to the Melamine Urea Formaldehyde (MUF) resin in identifying the best chemically modified waste rubber powder for interior plywood manufacturing using a laboratory press. Most of the plywood adhesives are formaldehyde based, which are not environmental friendly due to the formaldehyde emission, formaldehyde is considered as a carcinogenic agent. Due to the formaldehyde emission issue, plywood export to Europe and United State had been decreased. Therefore, the formaldehyde emission from the plywood is reduced. This work demonstrates the effect of filler at shear strength, water resistant and formaldehyde performance. Response surface methodology (RSM) software was used for identification of the optimum temperature and pressing time for wood adhesive performance. The optimum parameters investigated in this experiment was in the temperature range from 100 to 175°C at fixed pressing time at 150sec while in the time range from 50 to 450s at fixed prssing temperature at 125˚C. It was found that chemically modified waste rubber powder with 20% nitric acid had better plywood shear strenght, water resistant and formaldehyde emmision performance compared with other oxidizing agents solution. The optimum shear strength and formaldehyde emission performance of WRP was obtained by using pressing temperature 171.60˚C and time 269.27s was 1.37MPa and 0.7315mg/L. This work proved that extender is an important in enhancing the wood performance for wood adhesive. The sufficient amount of filler will increase the shear strength and decrease the formaldehyde emission of wood adhesive.